Mekanisme Penyimpanan dan Pemusnahan Barang Sitaan Narkotika (Studi Kasus Pada Kejaksaan Negeri Badung) - I Putu Krisna llham Wiantama; I Nyoman Gede Sugiartha; Ida Ayu Putu Widiati (Warmadewa Press, 2021)
There are many criminal cases of Narcotics in the jurisdiction of the Badung Prosecutor's Office, the procedure for storing confiscated objects of the State (Rupbasan) is regulated in Article 44 of the Criminal Procedure Code, then the destruction of confiscated Narcotics is carried out seven days after obtaining a court envoy who has permanent legal force as provisions of Law number 35 of 2009 concerning Narcotics. However, the implementation of this law still appears to be constrained by its implementation in the field. This study aims to explain the legal rules for storing and destroying confiscated Narcotics at the Badung Public Prosecutor's Office and describing the process of storing and destroying confiscated Narcotics at the Badung District Court. This study was designed using a normative method, namely examining library materials in relation to cases through a statutory approach. The data used are primary and secondary data. Data were collected by interviewing and documentation. The results showed the legal rules for the storage of confiscated Narcotics at Kasiswa Badung, according to Article 44 paragraph (1) of the Criminal Procedure Code, Perka BNN No. 7/2010, while for Destruction is regulated based on SE.IA Number: SE-018 / A / JA / 08/2015 dated 21 August 2015 is one of the legal bases, then the mechanism for storing and destroying confiscated Narcotics objects begins with the acceptance of delegation of authority from investigators to the public prosecutor to District Prosecutor's Office Badung by presenting the defendant and evidence to the District Prosecutor's Office Badung Badung. If the trial process has been completed and has retained legal force, the officer begins to collect and record various confiscated objects that will be destroyed, in this case divided according to the types of confiscated objects.